Influence of leadership attributes and motivation to lead on perceived career anchor of undergraduates in selected Malaysian public universities - Shazla, Aishath (2015)
The objective of this study was to examine the effect of leadership attributes and motivation to lead on perceived career anchor of undergraduates in selected Malaysian public universities. The respondents of this survey were 711 undergraduate students studying in public universities by using quota percentage sampling. Results indicate that the respondents have a high level of leader attributes and moderate levels of motivation to lead. Pearson correlation analysis showed Leadership attributes and motivation to lead (MTL), have significant relationships with career anchors. Furthermore, multiple regression analysis revealed that while leadership attributes was a significant predictor for all perceived career anchors. MTL predicted all career anchors, except technical and challenging career anchors. Finally, the study found Gender and levels of LA were significant factors in explaining the differences in undergraduates‟ preference for all types of career anchor. Levels of MTL only explained the differences of preference for six types of career anchors, except for life style and independence career. Program of study did not contribute to explaining any differences in preference of career anchor. Research findings supports the research hypothesis that undergraduates who have been exposed to leadership development have gained greater emotional and cognitive maturity that enable them to be more open to a broader range of career anchors. Hence, Universities should provide opportunities to their students in order to explore how their talents, attributes and values fit with occupations in the job market. The findings from this study provide a contribution to the knowledge of the relationship leadership and career anchor perception of undergraduate students.